2012
DOI: 10.1021/jp3006603
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Effects toward the Modulation of Magnetic Anisotropy and Design of Magnetic Systems with Desired Anisotropy Characteristics

Abstract: Magnetic anisotropy of a set of octahedral Cr(III) complexes is studied theoretically. The magnetic anisotropy is quantified in terms of zero-field splitting (ZFS) parameter D, which appeared sensitive toward ligand substitution. The increased π-donation capacity of the ligand enhances the magnetic anisotropy of the complexes. The axial π-donor ligand of a complex is found to produce an easy-plane type (D > 0) magnetic anisotropy, while the replacement of the axial ligands with π-acceptors entails the inversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 101 publications
2
19
1
Order By: Relevance
“…32,33 Being a non-cooperative property of an isolated molecule, the SIM behaviour depends on subtle and small structural variations in the metal coordination environment that directly determine the nature and magnitude of the local single-ion magnetic anisotropy, e.g. peripheral ligand modifications.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Being a non-cooperative property of an isolated molecule, the SIM behaviour depends on subtle and small structural variations in the metal coordination environment that directly determine the nature and magnitude of the local single-ion magnetic anisotropy, e.g. peripheral ligand modifications.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been recently proven that the addition or removal of ligands could be used to modulate the direction of the spontaneous magnetization. 13 Because the highest occupied 3d orbital and, respectively, the lowest unoccupied bring, in general, the largest contribution to the anisotropy, understanding the manner in which the metal states are populated may prove to be essential in both clarifying the origins of the molecular magnetic anisotropy as well as in reversibly controlling its orientation (from uniaxial to in plane and vice versa).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, from the above discussion, it is evident that the natural tendency of the electrons to flow towards the π‐acceptor NCS ligands is developed at a field strength higher than that of the critical field. It follows from our previous work that the π‐accepting tendency of the ligands exerts easy‐axis‐type magnetic anisotropy ( D <0) in a molecule 14. Thus, it can be concluded that the switch in the D value arises from metal‐to‐ligand back charge transfer in the molecule facilitated by exposure to the external electric field.…”
Section: Resultsmentioning
confidence: 89%
“…It follows from our previous work that the p-accepting tendency of the ligands exerts easyaxis-type magnetic anisotropy (D < 0) in a molecule. [14] Thus, it can be concluded that the switch in the D value arises from metal-to-ligand back charge transfer in the molecule facilitated by exposure to the external electric field. A similar and more interesting portrayal of the phenomenon is found in the spin density plots depicted in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation